PERSEPSI PENGUNJUNG TERHADAP OBJEK WISATA PANTAI GUMUMAE DI KECAMATAN BULA KABUPATEN SERAM BAGIAN TIMUR - Nabila Keliobas; Yosevita Theodora Latupapua; C K Pattinasarany (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
Visitors 'perceptions of the Gumumae Beach tourist attraction in Bula District, East Seram Regency were research aimed to know visitors' perceptions of Gumumae Beach attractions in Bula District, East Seram District. The selection of research locations was conducted purposively in November-December 2018, in this study the data collection method used was in the form of direct observation in the field, distribution of questionnaires / interviews, documentation, and literature study. Analysis of research data using qualitative descriptive analysis methods to answer research objectives based on information obtained from field observations. From the results of the study, it can be seen that visitors' perceptions of attraction from Gumumae Beach attractions give an assessment that the beach scenery is an interesting with a percentage of 80%. Visitors’ perception of the facility/amenity the attractions provide an assessment officer friendliness associated with a good percentage of 46.67%, mininum meal service is quite good 56.67%, security / safety is not guaranteed 48.33 coast, beach cleanliness less good 51.67%, additional facilities need to be done 100%, satisfaction in making visits is 50% satisfied , and visitors' perceptions of accessibility on Gumumae Beach attractions are valued at 86.67% and smooth object public transportation modes 48.33%.